The sociology of medical screening : critical perspectives, new directions - Armstrong, Natalie; Eborall, Helen (Chichester, West Sussex, U.K. : Wiley-Blackwell, 2013)
"The Sociology of Medical Screening: Critical Perspectives, New Directions presents a series of readings that provide an up-to-date overview of the diverse sociological issues relating to population-based medical screening. Features new research data in most of the contributions. Includes contributions from eminent sociologists such as David Armstrong, Stefan Timmermans, and Alison Pilnick. Represents one of the only collections to specifically address the sociology of medical screening"--Provided by publisher.
"Originally published as v. 34, issue 2 of The sociology of health & illness"--Title page verso.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Medical screening; Social medicine; Mass Screening; Genetic Testing; Sociology, Medical; HEALTH & FITNESS -- Diseases -- Genetic; Medical screening; Social medicine; Electronic books